Apartheid Politics in South Africa - Okuma Lelo (GoAcademica Research & Publishing, 2020)
Racial discrimination is a very big problem and is found in several countries such as the United States, Britain and the most dominant in South Africa with Apartheid politics. Therefore, South Africa is the focus of the fight against racism towards the realization of justice. The word Apartheid means